DEVELOPMENT OF QUICK POWER QUALITIES OF STUDENTS IN RUNNING AND LONG JUMP - Mukimov , O.E (Innovative Development in Educational Activities, 2024)
This article focuses on the development of quick power qualities in students for running and long jump. It provides insights and strategies to enhance power output, speed, and explosiveness, which are essential for success in these athletic disciplines. The article emphasizes key factors such as nutrition, recovery, plyometric progression, strength-to-weight ratio, mental conditioning, and cross-training. It also highlights the significance of sleep, video analysis, and long-term athlete development. Additionally, the article discusses sport-specific conditioning, resistance training, core strengthening, speed and agility drills, flexibility and mobility training, prehabilitation exercises, interval training, track and field equipment, and recovery strategies. By incorporating these principles and practices, educators and coaches can help students optimize their power qualities and reach their athletic potential in running and long jump.